Dark galaxies and lost baryons : proceedings of the 244th symposium of the International Astronomical Union held in Cardiff, Wales, United Kingdom, June 25-29, 2007 - International Astronomical Union. Symposium (244th : 2007 : Cardiff, Wales); Davies, Jonathan S.; Disney, Michael (Cambridge : Cambridge University Press, 2008)
Includes bibliographical references and index.